Counseling Andy - Pierce, J Rush, Jr. (Journal of pastoral care & counseling, 2025)
In this first-person narrative, the Dean instructs a young supervising physician to counsel a medical student about why he should not talk to patients about his religion. The essay reflects some of the emotions, ethical considerations and ambiguities that caregivers face in these situations.